Poly(ionic liquid) binders as ionic conductors and polymer electrolyte interfaces for enhanced electrochemical performance of water splitting electrodes. Issue 7 (16th May 2018) - Spanos, Ioannis; Neugebauer, Sebastian; Guterman, Ryan; Yuan, Jiayin; Schlögl, Robert; Antonietti, Markus
Abstract : A PIL blocks metals at the electrode, while it is permeable to water, hydroxy ions and the as-generated oxygen. Abstract : A poly(ionic liquid) (PIL) was used as a binder for NiCo oxide nanopowder in a water electrolysis standard assay to explore the role of polymers in a model electrocatalytic device. The comparison to technical standard binders such as Nafion™ or Fumion™ ionomers showed that the PIL improves the cycling stability under accelerated ageing conditions as well as the activity.